The attitude of al-Khatīb Al-Shirbīni of the poetic necessity - Kasur, Ahmed; el-Sawahly, Moustafa (Al-Ḍād Journal, 2020)
This research deals with an old and renewable issue in Arabic grammar. It is the case of poetic necessity, which represents a major conflict between the grammarians and poets, and non-specialists may consider it as a disregard for the grammatical rules and a break of discipline, but in fact, it is an evidence of the great flexibility enjoyed by the Arabic syntax. The research aims to clarify the position of Al-Khatib Al-Sharbini to this issue through the descriptive and analytical approach via extrapolating his grammatical books, so that the statement of his position to this issue can depend on his texts, not on what is said by the others about him. This is required by the explanation about the definition of poetic necessity as the language and the term, explaining the extent of different opinions among the grammarians about it, presenting their views on the explanation of this term, especially Sibawayh and Ibn Malik, then explaining the position of Al-Khatib Al-Sharbini about it. It became clear to the researcher that al-Khatib al-Sharbini was not against what was settled by the majority of grammarians since the era of Sibawaih. However, Sibawayh did not use the term â€œnecessityâ€ in his book, but the grammarians had understood from the content of his position towards this issue that it is what occurs in the poetry, not in the prose, whether the poet has a choice or not, on the contrary of position taken by Ibn Malik, who made it limited to that the poet had no choice about it. The four types of poetic necessity were mentioned in the writings of Al-Khatib al-Sharbini, that are the decrease, increase, changing place, and substitution. The researcher noticed that al-Khatib al-Sharbini did not distinguish between poetic necessity and the irregular despite what the majority of grammarians settled on. This confirms that Al-Khatib El-Sherbiny was not a copycat like many scholars of his era, but rather has his own attitude stemming from his personal vision based on the evidence.